Dominated flow parameters applied in a recirculation microbial fuel cell. (December 2020) - Wang, Chin-Tsan; Chen, Yan-Ming; Tang, Raymond Chong Ong; Garg, Akhil; Ong, Hwai-Chyuan; Yang, Yung-Chin
Graphical abstract: Flow dimensionless numbers applied in a recirculation microbial full cells and its outcome. Highlights: Using dimensional analysis as mechanical design approach to enhance power performance of microbial fuel cell. Reynolds number has dominant effect in comparison with Sherwood and Péclet numbers. Re∞ = 1.6 × 10 1 was found to be optimal in a recirculation MFCs. Abstract: Scaling up of microbial fuel cells is a challenge for practical applications in wastewater treatment. In addition, the flow control is an important aspect for the electrochemical reactions occurring at the electrodes are influenced by fluid motions. By using dimensionless parameter analysis fluid regimes can be investigated in different scales of reactors. In this study, four important dimensionless flow parameters such as Reynolds number, Péclet number, Schmidt number, and Sherwood number were used for systematic analysis of hydrodynamic effects and power performance of recirculation mode microbial fuel cells together with computational fluid dynamics method. Results showed that the higher value of Reynolds number enhanced the convective flow of anolyte due to the dominant inertial forces in the flow field. Therefore, Reynolds number of 1.6 × 10 1 were obtained high mass transfer coefficient of 4.76 × 10 −7 m s -1 and thin diffusion layer thickness of 2.52 × 10 -3 m. Maximum power density and limited current density of 2422.8 mW m -2 and 4736.4 mA m -2 were obtained respectively which were higher than Reynolds number of 0 by 1.61 and 1.69 times. These findings shall be useful for effective recirculation flow mode MFCs power production and have a great possibility for large scale applications.